An Agile Systems Engineering Analysis of Socio‐technical Aspects of a University‐built CubeSat. Issue 3 (6th October 2021) - Honoré‐Livermore, Evelyn; Garrett, Joseph L.; Lyells, Ron; Angier, Robert (Rock); Epps, Bob
ABSTRACT: System development teams often face challenges outside of pure technical problems. There are unpredictable circumstances in many areas including customer needs, personnel changes, and sociotechnical issues that can span across the development organization such as knowledge management and goal alignment. This paper presents the results of an exploratory case study on a university CubeSat team developing an Earth Observation satellite. Formal analysis of agile systems engineering helps improve success throughout the CubeSat lifecycle. We apply the INCOSE Agile systems engineering WG decision guidance method for applying agile system engineering method to identify areas in which the project organization can improve to become more agile in three specific problem spaces: customer problem space, solution space, and product development space. The analysis process led to valuable insights about how the project organization of an academic project differs from that of industry. Additionally, the results indicate that areas such as stakeholder management and support environment could be factors that would benefit more from agile responsiveness.